L'Islam spiegato ai miei studenti. Undici lezioni sul diritto islamico: II edizione riveduta e ampliata - Fiorita, Nicola (Studi e saggi, 2010)
Beyond all instrumentalisation, the rooted Muslim presence in Italy raises problems of various kinds that are not easy to resolve. Inevitably, the need to comprehend the content of the principles and the rules governing Islam is destined to increase, expanding from the narrow circle of the specialists to the broader group of legal, social and cultural workers. This handy book, originally designed to give students easy-to-use teaching material, attempts to meet this demand via eleven lessons that address the specific profiles and the most topical issues of the Islamic legal system: the sources of the law, marriage, human rights, the holy war, female genital mutilation, the veil and the birth of the Islamic banks. The final section of the book devotes ample space to the solutions which the western legal systems have (or have not) elaborated to respond to the specific requirements of Muslims living in Europe